Effect of breathing hypoxic gas mixtures followed by irradiation on tumour cell survival in experimental mouse tumors - Hendrikse, Andre Stephen (Department of Philosophy, 2023)
It is generally accepted that most tumours contain radioresistant hypoxic cells, which limit the effectiveness of photon radiation. This dissertation outlines an attempt to i increase the sensitivity of mouse tumours to X- and gamma radiation by reducing the fraction of hypoxic cells in tumours. It is proposed that this can be achieved by making the tumour bearing animals breathe a hypoxic gas mixture for a period of time and then returning them to a normoxic or hyperbaric oxygen (HBO) environment just prior to and for the duration of delivery of radiation. The effect of breathing 8% oxygen for 72 hours prior to radiation (single X-ray dose of 11 Gy) in air or in HBO on the regrowth delay of CaNT tumours and 3-methylcholanthrene-induced murine rhabdomyosarcomas was compared with radiation alone. No differences in regrowth delay were observed in the case of the CaNT tumour between the mice that received pre-treatment and radiation and those that received radiation alone. In the rhabdomyosarcoma an increase in regrowth delay was observed in the mice that were exposed to the 8% oxygen environment for a 72-hour period prior to being irradiated. These findings are discussed with reference to the different hypoxic cell fractions which were determined for each tumour type (CaNT 54%; rhabdomyosarcoma 27%). The response of the Fib/T tumour grown in WHT mice to 60co gamma rays (delivered in air or in HBO) where mice were exposed to different hypoxic pre-treatments (8%, 10% or 15% oxygen) lasting either 48 hours or 72 hours was compared to that obtained where mice were pre-treated with air, using an in vitro colony forming excision assay. The response of the Fib/T tumour to radiation was improved by a 48 hour and 72-hour exposure of the WHT mice to 8%, 10% and 15% oxygen. However, the greatest sensitization was achieved where mice were kept in an 8% oxygen environment for 48 hours before radiation. These results are interpreted and discussed in relation to two adaptation mechanisms, viz. increased haemoglobin levels and increased 2,3-DPG concentrations, that were shown to operate where mice were exposed to a reduced oxygen environment. Furthermore, the importance of the "increased oxygen availability" model relative to the "reduced cord radius" model is assessed. Where mice, pre-treated with air, were irradiated in HBO, a similar tumour response was observed compared to where mice were pre-treated with 8% oxygen for 48 hours but irradiated in air. Where mice were exposed to two equal fractions of radiation, spaced by an interval. Of 24 hours, the greatest tumour response to radiation was observed where the mice were pre-treated with 8% oxygen for 48 hours and then returned to this environment for the 24-hour interval between fractions. If both fractions of radiation were delivered in HBO, an increase in tumour radiation damage was produced compared to where radiations were delivered in air. The response of the Fib/T tumour to single dose neutron radiation (delivered to air-breathing mice) was determined where mice were either pre-treated for 48 hours with 8% oxygen or with air. Results indicated that a 48-hour 8% oxygen pre-treatment was less efficacious in sensitizing the Fib/T tumour to neutron radiation than it was in sensitizing the Fib/T tumour to 60co gamma radiation. The activity of the scavenger enzymes, catalase and glutathione peroxidase, and a related enzyme in the antioxidant system (glutathione reductase), as well as the content of glutathione were determined in the Fib/T tumour of mice before and after exposure to 8% oxygen. This hypoxic environment was found to produce no significant change in the activity of either of the three enzymes or in glutathione levels. iii Finally, the findings reported in this thesis are discussed in relation to possible adaptation in the clinical radiotherapy situation.